New Zealand super rugby injury surveillance: match injuries from 2015-2018 - Salmon, D.; Murphy, I.; Quarrie, K.; MacLeod, G.; Singh, A.; Letts, A.; Roche, J.; Robinson, D.; Swan, M.; Dorfling, T.; Shaw, C.; Rottier, K.; et al. (British Journal of Sports Medicine, 2021)
Background Rugby union is a collision-based sport, as such the occurrence of injuries resulting in time-loss from participation is inevitable. In 2015 New Zealand Rugby (NZR) began an injury surveillance program with all NZ-based Super Rugby teams to capture all time-loss injuries.